Semaphorin 3F (SEMA3F) influences patient survival in esophageal adenocarcinoma - Knipper, Karl; Lyu, Su Ir; Jung, Jin-On; Alich, Niklas; Popp, Felix C.; Schröder, Wolfgang; Fuchs, Hans F.; Bruns, Christiane; Quaas, Alexander; Nienhüser, Henrik; Schmidt, Thomas (Scientific reports, 2024)
In esophageal adenocarcinoma, the presence of lymph node metastases predicts patients' survival even after curative resection. Currently, there is no highly accurate marker for detecting the presence of lymph node metastasis. The SEMA3F/NRP2 axis was initially characterized in axon guidance and recent evidence has revealed its significant involvement in lymphangiogenesis, angiogenesis, and carcinogenesis. Hence, the objective of this study was to elucidate the roles of SEMA3F and its receptor NRP2 in esophageal adenocarcinoma. We conducted an immunohistochemical evaluation of SEMA3F and NRP2 protein expression in 776 patients with esophageal adenocarcinoma who underwent Ivor-Lewis esophagectomy at the University Hospital of Cologne. Total and positive cancer cell counts were digitally analyzed using QuPath and verified by experienced pathologists to ensure accuracy. Positive expression was determined as a cell percentage exceeding the 50th percentile threshold. In our cohort, patients exhibiting SEMA3F positive expression experience significantly lower pT- and pN-stages. In contrast, positive NRP2 expression is associated with the presence of lymph node metastases. Survival analyses showed that the expression status of NRP2 had no impact on patient survival. However, SEMA3F positivity was associated with a favorable patient survival outcome (median OS: 38.9 vs. 26.5 months). Furthermore, SEMA3F could be confirmed as an independent factor for better patient survival in patients with early tumor stage (pT1N0-3: HR = 0.505, p = 0.014, pT1-4N0: HR = 0.664, p = 0.024, pT1N0: HR = 0.483, p = 0.040). In summary, SEMA3F emerges as an independent predictor for a favorable prognosis in patients with early-stage esophageal adenocarcinoma. Additionally, NRP2 expression is linked to a higher risk of lymph node metastases occurrence. We hypothesize that low SEMA3F expression could identify patients with early-stage tumors who might benefit from more aggressive treatment options or intensified follow-up. Furthermore, SEMA3F and its associated pathways should be explored as potential tumor-suppressing agents.